Indicators in the Performance Evaluation Rubric for Supervision Consultants in Toll Road Construction Projects - Rarasati, Ayomi Dita; Rahman, Wahyu Putra (Journal La Multiapp, 2025)
The construction of toll roads is a key government program aimed at enhancing public productivity and accelerating national economic growth. To ensure that toll road construction meets the desired quality, time, and cost objectives, the involvement of competent supervision consultants is essential. However, suboptimal performance of these consultants often leads to less-than-ideal project outcomes. This study aimed to analyse the performance evaluation indicators of supervision consultants and incorporate them into a comprehensive performance assessment rubric for supervision consultants in toll road construction projects. The research methodology combined literature review, questionnaire surveys, and expert interviews for data collection. Then, each indication is ranked and weighted using the Rank Order Centroid (ROC) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) approaches. The results showed that respondents and experts identified 18 important indicators grouped into three categories soft skills, technical skills, and project supervision which can be used in a validated performance assessment rubric for evaluating supervision consultants in toll road construction projects.